MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN TULISAN BRAILLE MELALUI SISTEM MENGGOLD BAGI ANAK TUNANETRA - Bainal - Isnaini (Jurnal Penelitian Pendidikan Khusus, 2013)
The purpose of this study were: 1) to describe the implementation of the learning process improvements to improve reading skills beginning with menggold system and 2) Prove whether menggold system can improve reading skills in children with visual impairments SLB SLB class II in South Solok Bina Nagari. Type of research is a classroom action research (classroom action research) with two cycles performed in the form of collaboration with colleagues. Research subjects are two blind children second grade and one teacher. Data obtained through observation and tests. Then analyzed qualitatively and quantitatively.The results showed that 1) the process of learning to improve reading skills in children with visual impairments through the system menggold done in two cycles. Cycle I made six sessions and the second cycle of five (5) meetings. 2) The results of the study with the system menggold reading skills in children with visual impairment are increased. This proved: before treatment (assessment) value reading skills in children with visual impairment in children: R for (55.6) and Ir (51.1). I cycle an increase in the ability to read the R into (78.9) and Ir is (72.2). While on the second cycle is increasing, where R into (100) and Ir (96.7). Thus, we can conclude that sitem menggold can help improve reading skills in children with visual impairment. Advised on the school, teachers and researchers can use the system further to menggold in improving reading skills in other blind children.